Nurse Practitioner and General Practitioner Error Rates in a Large Digital Health Service: A Retrospective Cohort Analysis - Louis Talay; Matt Vickers; Daisy Lu (Nursing Reports)
Background: Nurse practitioners have been prescribing medication within a narrow scope of practice throughout the world for several decades as a means of meeting rising demand for community health services. Prominent medical bodies have alleged that the Australian government’s decision to remove the need for general practitioner collaboration in the context of a nurse practitioner prescribing medication compromises patient safety. Objectives: This study aimed to determine whether nurse practitioner prescribing increases patient risk relative to general practitioner prescribing in a large digital health service. Methods: Investigators retrospectively analyzed prescription errors from all audited consults of the Eucalyptus Australia service over a 6 month period between 1 October 2023 and 31 March 2024. Results: Of the 8359 consults, errors were observed in 911 (14.22%) of NP and 417 (21.37%) of general practitioner consults and this difference was found to be statistically significant, X2 (1, N = 8359), =57.33, p ≤ 0.001. No statistically significant difference was observed in the incidence of high-risk or never events between nurse practitioners and general practitioners. Most high-risk and never events pertained to medical contraindications, insufficient side-effect counselling, and the insufficient assessment of a patient’s medical history. Conclusion: These findings suggest that nurse practitioners are capable of safely performing patient assessments and prescribing medications for a select range of conditions in digital health services.